2022
DOI: 10.3389/fpls.2021.693680
|View full text |Cite
|
Sign up to set email alerts
|

Generation Mean Analysis Reveals the Predominant Gene Effects for Grain Iron and Zinc Contents in Pearl Millet

Abstract: Pearl millet [Pennisetum glaucum (L.) R. Br.] is a climate-resilient dryland cereal that has been identified as a potential staple food crop that can contribute to alleviating micronutrient malnutrition, particularly with respect to grain iron (Fe) and zinc (Zn) contents, in Sub-Saharan Africa and India. In this regard, an understanding of the inheritance pattern of genes involved in Fe and Zn contents is vital for devising appropriate breeding methods to genetically enhance their levels in grains. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…For grain Fe and Zn concentration, the relatively high proportions of GCA over SCA, the high ratio of additive and dominance variance, and the predictability ratio close to unity (0.97 for iron and 0.93 for zinc) suggest that these traits are predominantly under the control of additive gene action. This is in line with previous studies that reported these traits being under additive gene action in pearl millet (Velu, 2006;Rai et al, 2007;Govindaraj et al, 2013;Kanatti et al, 2014;Kanatti et al, 2016;Pujar et al, 2022). With respect to the agronomic traits, flowering time, plant height, panicle length, panicle girth, panicle compactness, and downy mildew incidence had a high predictability ratio, implying that these traits are under additive genetic control.…”
Section: Estimates Of Variance and Genetic Variance Componentssupporting
confidence: 90%
“…For grain Fe and Zn concentration, the relatively high proportions of GCA over SCA, the high ratio of additive and dominance variance, and the predictability ratio close to unity (0.97 for iron and 0.93 for zinc) suggest that these traits are predominantly under the control of additive gene action. This is in line with previous studies that reported these traits being under additive gene action in pearl millet (Velu, 2006;Rai et al, 2007;Govindaraj et al, 2013;Kanatti et al, 2014;Kanatti et al, 2016;Pujar et al, 2022). With respect to the agronomic traits, flowering time, plant height, panicle length, panicle girth, panicle compactness, and downy mildew incidence had a high predictability ratio, implying that these traits are under additive genetic control.…”
Section: Estimates Of Variance and Genetic Variance Componentssupporting
confidence: 90%
“…The significant positive effects for pooled [h] and negative estimates for [l] showed the presence of duplicate types of gene interactions, which means dominant genes with small cumulative effects controlled the inheritance of the VL in both the crosses, the IL in C 1 as well as the IN and PL in C 2 (Table 2 and 3). Therefore, the selection should be delayed until a high level of gene fixation is attained and population improvement methods would be more effective to break the undesirable linkage and accumulate desirable genes (Pujar et al 2022). The significant contribution of the epistasis in controlling the inheritance of the VL and IL in pumpkins was earlier reported by Mohanty et al (1999); Pandey and Rao (2010); Almeida et al (2020); Yadav et al (2021) and in the summer squash by Kaur et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Partitioning of genetic variance into its all the probable components i.e, additive, dominance and all types of epistasis with regard to individual cross therefore assumes immense value in formulating an effective and sound breeding programme (Alvarez-Castro and Le Rouzic, 2015). Among the common approaches followed to understand the nature of gene effect, generation mean analysis using first degree statistics is an accurate one and gives detailed account of various gene effects and also the quality of the genes carried by the parents (Pujar et al 2022). It is also an important statistical tool for identification of epistasis using various basic generations from a cross between two parents (Bano et al 2017).…”
Section: Introductionmentioning
confidence: 99%